Current management of diabetes patients with COVID-19. Issue 2 (4th March 2023) - Misra, Arup Kumar; Rangari, Gaurav; C, Madhavrao; Sharma, Sushil
ABSTRACT: Introduction: Diabetes mellitus (DM) and the 2019 coronavirus (COVID-19) appear to interact in both directions. There is mounting proof that patients with DM have a worse COVID-19 prognosis than those without it. Pharmacotherapy is also known to affect in view of the possible interplay between drugs and the pathophysiology of the above conditions in a given patient. Areas covered: In this review, we discuss the pathogenesis of COVID-19 and its connections with diabetes mellitus. We also analyze the treatment modalities for COVID-19 and diabetes patients. The possible mechanisms of the different medications and their management limitations are also systematically reviewed. Expert opinion: COVID-19 management as well as its knowledge base is changing constantly. The Pharmacotherapy and the choice of drugs also need to be specifically considered in view of the concomitant presence of these conditions in a patient. Anti-diabetic agents must be carefully evaluated in diabetic patients in view of the disease's severity, blood glucose level, appropriate treatment, and other components that could aggravate adverse events. A methodical technique is anticipated to enable the safe and rational use of drug therapy in COVID-19-positive diabetic patients to take.